2019
DOI: 10.1016/s2213-2600(19)30114-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline or albumin fluid bolus in resuscitation: evidence from re-analysis of the FEAST trial

Abstract: Summary Background Fluid resuscitation is the recommended management of shock, but increased mortality in febrile African children in the FEAST trial. We hypothesised that fluid bolus-induced deaths in FEAST would be associated with detectable changes in cardiovascular, neurological, or respiratory function, oxygen carrying capacity, and blood biochemistry. Methods We developed composite scores for respiratory, cardiovascular, and neurological function usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 40 publications
3
52
0
4
Order By: Relevance
“…The FEAST trial evaluated the role of fluid bolus therapy in the resuscitation of children in Africa with shock and life-threatening infections with severe febrile illness and impaired perfusion (mostly malaria), and reported higher 48-h mortality in those who received boluses of either saline or 5% albumin, as compared with a no bolus control group who received maintenance fluids 127 . A recent reanalysis of the FEAST trial found that worsening hyperchloremic acidosis, due to the chloride content of the saline or 5% albumin boluses, was a major contributor to the increased mortality risk 128 . This raises the possibility that lower-volume fluid therapy with buffered solution or higher-percentage HSA solution might help to minimize mortality in this setting, although this requires further study 128,129 .…”
Section: Infectious Diseases and Febrile Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The FEAST trial evaluated the role of fluid bolus therapy in the resuscitation of children in Africa with shock and life-threatening infections with severe febrile illness and impaired perfusion (mostly malaria), and reported higher 48-h mortality in those who received boluses of either saline or 5% albumin, as compared with a no bolus control group who received maintenance fluids 127 . A recent reanalysis of the FEAST trial found that worsening hyperchloremic acidosis, due to the chloride content of the saline or 5% albumin boluses, was a major contributor to the increased mortality risk 128 . This raises the possibility that lower-volume fluid therapy with buffered solution or higher-percentage HSA solution might help to minimize mortality in this setting, although this requires further study 128,129 .…”
Section: Infectious Diseases and Febrile Illnessmentioning
confidence: 99%
“…A recent reanalysis of the FEAST trial found that worsening hyperchloremic acidosis, due to the chloride content of the saline or 5% albumin boluses, was a major contributor to the increased mortality risk 128 . This raises the possibility that lower-volume fluid therapy with buffered solution or higher-percentage HSA solution might help to minimize mortality in this setting, although this requires further study 128,129 .…”
Section: Infectious Diseases and Febrile Illnessmentioning
confidence: 99%
“…A recent secondary analysis of the Fluid Expansion as Supportive Therapy study demonstrated the relevance of respiratory, cardiovascular, and central nervous system dysfunction in identifying patients at a greater risk of mortality, further supporting this approach. 18 The 2005 Pediatric Sepsis Consensus 19 thresholds for abnormal HR and RR, used in both SIRS and the age-adjusted qSOFA, were based on values that were likely determined through clinical consensus. 20 In contrast, evidencebased sets of reference ranges have since been developed, on ED 21 and hospitalized patients, 22 which may be more discriminative in the febrile ED population.…”
mentioning
confidence: 99%
“…In one of the conditions known to cause dehydration without systemic inflammation, diabetic ketoacidosis, Kuppermann and Glaser found that large volume fluid resuscitation was not associated with an increased risk of developing cerebral oedema (injury). This stands in contrast to the finding that FBT in children with a febrile illness and poor perfusion was associated with cerebral and pulmonary oedema . Further study is needed to define the patient groups that may benefit or that may be harmed by FBT.…”
Section: Discussionmentioning
confidence: 62%